2011
DOI: 10.4049/jimmunol.1003491
|View full text |Cite
|
Sign up to set email alerts
|

Coronin 1-Mediated Naive T Cell Survival Is Essential for the Development of Autoimmune Encephalomyelitis

Abstract: Autoimmune encephalomyelitis is a disease of the CNS that can develop when an initial peripheral inflammatory stimulus is followed by infiltration and reactivation of T lymphocytes in the CNS. We report a crucial role for coronin 1, which is essential for maintenance of the naive T cell pool, for the development of murine experimental autoimmune encephalomyelitis (EAE), a model for multiple sclerosis. In the absence of coronin 1, immunization with myelin oligoglycoprotein (MOG35–55) peptide largely failed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 45 publications
(62 reference statements)
2
22
1
Order By: Relevance
“…On one hand, the transfer of T cells baring the point mutation described above was sufficient to reduce lupus-like diseases (15). On the other hand, the transfer of wildtype CD4 ϩ T cells before immunization did restore the susceptibility of Coro1a-deficient mice to EAE induction (17). The later experimental approach suggests that Coro1a-deficient APCs are fully capable of priming T cells and promoting effector T cell differentiation as long as those T cells express Coro1A.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…On one hand, the transfer of T cells baring the point mutation described above was sufficient to reduce lupus-like diseases (15). On the other hand, the transfer of wildtype CD4 ϩ T cells before immunization did restore the susceptibility of Coro1a-deficient mice to EAE induction (17). The later experimental approach suggests that Coro1a-deficient APCs are fully capable of priming T cells and promoting effector T cell differentiation as long as those T cells express Coro1A.…”
Section: Discussionmentioning
confidence: 97%
“…This point mutation introduces a stop codon in the middle of the protein, leading to a truncated version of Coro1A, which fails to localize to the plasma membrane. Furthermore, conventional Coro1a-deficient mice, generated independently in distinct laboratories, were protected against the development of severe signs of EAE induced by immunization with the MOG peptide (14,17). This phenotype has been attributed to alterations of intrinsic T cell function, namely impaired migration, cell activation, and survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mice deficient in the p57/coronin-1 gene, differentiation and chemokine-mediated trafficking of T cells were severely impaired (22,24,25). It was further demonstrated that the developments of experimental autoimmune encephalomyelitis (26,27) and lupus-like autoimmune disease (28) were suppressed in mice with genetic defects of p57/coronin-1. These studies suggested the potential relevance of p57/coronin-1 to allergic and autoimmune diseases.…”
mentioning
confidence: 82%